(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Tonsillectomy is one of the most common procedures performed by otolaryngologists. It is a surgical operation that removes both palatine tonsils from the tonsillar fossa. It is typically performed in youngers for recurrent tonsillitis and tonsillar hypertrophy. This study was done to compare the dissection and diathermy methods of tonsillectomy and evaluate their advantages and disadvantages during surgery and convalescence. This study was a retrospective analysis of 400 patients from January 2015 to January 2020 in Otorhinolaryngology and Head-Neck Surgery department of Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur. Out of 400 patients 200 patients underwent tonsillectomy by dissection method and rest 200 patients underwent electrocautery method. Total 400 patients were analyzed separately their hospital stay, blood loss per-operatively, complications in each method and overall outcome of the patients. The overall hospital staying in both types was 1-3 days. The average intra operative blood loss was 5-7 ml in cautery and average 50 ml in dissection method. The average operative time was 25-30 minutes in dissection method and 10-15 minutes was in electrocautery. We found higher amounts of blood loss and intra - operative time in dissection method than electrocautery. The chance of secondary haemorrhage was more in electrocautery method than dissection method. Pain, scar formation, odynophagia were more in cauterization method. Complete healing time was more in cauterization method than dissection method. There was no death in both methods. Although per-operative blood loss, operation time were less in cauterization method but post operative bleeding, pain, odynophagia and infection were more in electro cauterization method. In both methods, there were some advantages and some disadvantages. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 40-44